Are banks in Europe too big to fail or too big to save? - Silva, Catarina de Figueiredo Bettencourt Moreira da (2021)
The financial crisis of 2007-2009 raised concerns regarding countries’ abilities to rescue their largest banks should a new crisis emerge. By focusing on European Union banks from 2001 through 2019, this dissertation investigates the impact of both absolute and systemic bank size on a bank’s valuation and CDS spreads. We find that a bank’s market-to-book ratio is negatively related to its natural logarithm of total assets and liabilities-to-GDP ratio. We further established that CDS spreads seemingly increase in a dynamic market response to changes in bank’s absolute size. These results suggest that large banks can increase their value by downsizing or splitting up. Our findings also show that in the aftermath of the financial crisis, most banks in our sample reduced their systemic size. This decrease may indicate that while banks in the European Union were certain of a too big to fail status with the inference that governments would rescue them if necessary, this certainty mostly vanished post 2009. The events that followed the crisis revealed to several banks that they were in fact, too big to save, leading many to adapt to this new reality by downsizing.